Validity of smartphone pedometer applications. (December 2015) - Orr, Krystn; Howe, Holly; Omran, Janine; Smith, Kristina; Palmateer, Tess; Ma, Alvin; Faulkner, Guy
Abstract Background Given the widespread use of smartphone pedometer applications and the relatively limited number of published validity tests, this study examined the validity of three popular commercial smartphone pedometer applications (i.e., Accupedo, Moves, and Runtastic Pedometer). Participants Convenience samples of males and females were recruited for laboratory tests [n = 11; mean: aged 24.18 years (±3.06)] and a free-living test [n = 18; mean: aged 28.78 years (±9.52)]. Methods Five conditions were assessed: (a) 20-step test, (b) 40-step stair climbing, (c) treadmill walking and running at different speeds, (d) driving, and (e) 3-day free-living. The Yamax SW-200 pedometer and observed step counts were used as criterion measures. Results Analyses identified an unacceptable error percentage in all of the applications compared to the pedometer. Conclusions Given the inaccuracy of these applications, caution is required in their promotion to the public for self-monitoring physical activity and in their use as tools for assessing physical activity in research trials.